Dinuclear Lanthanide Complexes Based on a Schiff‐base Ligand: Free Lattice Solvent Inducing the Single Molecule Magnet Behavior of Dy2 Compound. Issue 23 (25th October 2018) - Ge, Yu; Qin, Yaru; Cui, Yanfeng; Pan, Yangdan; Huang, Yuan; Li, Yahong; Liu, Wei; Zhang, Yi‐Quan
Abstract: Syntheses, crystal structures and magnetic properties are described for a series of seven‐coordinate dinuclear lanthanide complexes of compositions Dy2 L2 (1 ) (H3 L=2‐ {[bis(2‐hydroxy‐3‐ethoxybenzyl)(aminoethyl)amino]methyl}phenol) and Ln2 L2 ⋅MeCN (Ln=Dy (2 ), Sm (3 ), Eu (4 ), Gd (5 ), Tb (6 ), Ho (7 )). The reaction of Dy(NO3 )3 ⋅6 H2 O with one equivalent of H3 L at 70 °C in DMF/EtOH under autogenous pressure gave compound 1 . Complexes 2 –7 were prepared by means of the same method as that used for1, except DMF was replaced by MeCN as the reaction solvent and Dy(NO3 )3 ⋅6 H2 O was changed to the corresponding lanthanide salts. Complexes 1 –7 possess the similar Ln2 cores bridged by μ2 ‐phenoxyl oxygen atoms. The slight difference between1 and2 –7 arises from the existence of free MeCN molecule in2 –7 . The purposeful introduction of solvent MeCN molecule changes the crystal system from triclinic for1 to monoclinic for2 and alters the Dy—O–Dy angles and Dy⋅⋅⋅Dy distances, consequentially resulting into dramatic influences on the magnetic properties of1 and2 . Complex 1 shows no SMM character, while compound 2 with free MeCN molecule exhibits a field‐induced slow magnetization relaxation behavior. Complete active space self‐consistent field (CASSCF) calculations were performed on two Dy2 compounds to rationalize the observed difference in the magnetic behavior. Theoretical calculations reveal that the energy gap between the lowest two Kramers doublets of individual Dy III fragment for2 is higher than those of1 (1_ a and1_ b ). This conlusion is consistant with the experimental result that complex 2 exhibits better magnetic properties. This work proposes an ingenious strategy for inducing the SMM behavior in the Dy2 compounds. Abstract : The involvement of MeCN molecule in Dy2 L2 (1 ), which did not display SMM properties, results in the formation of SMMs Dy2 L2 ⋅MeCN (2 ). This work proposes an ingenious strategy for inducing the single molecule magnet (SMM) behavior in Dy2 compounds.